Van Loon, H., De Nie, G., Op de Coul, M., Van Egmond, P. (eds.) (2018). Prayer and the Transformation of the Self in Early Christian Mystagogy - Jacobsen, Anders-Christian (ARYS. Antigüedad: Religiones y Sociedades, 2020)
VAN LOON, HANS, DE NIE, GISELLE, OP DE COUL, MICHIEL, and VAN EGMOND, PETER (eds.) (2018). Prayer and the Transformation of the Self in Early Christian Mystagogy, Late Antique History and Religion, 18. Leuven: Peeters. 482 pp., 123,63€ [ISBN 978-9-0429-3611-9] [Book review]